2004
DOI: 10.1111/j.1460-9568.2004.03658.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery and axonal growth following spinal cord transection is accelerated by sustained l‐DOPA administration

Abstract: The eel, Anguilla anguilla, as with other fish species, recovers well from spinal cord injury. We assessed the quality of locomotion of spinally transected eels from measurements made from video recordings of individuals swimming at different speeds in a water tunnel. Following transection of the spinal cord just caudal to the anus, the animals displayed higher tail beat frequencies and lower tail beat amplitudes than before surgery, owing to the loss of power in this region. Swimming performance then progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…2004). Furthermore, functional recovery and axonal growth after spinal cord transection are accelerated by sustained l ‐DOPA administration (Doyle and Roberts 2004).…”
Section: Discussionmentioning
confidence: 99%
“…2004). Furthermore, functional recovery and axonal growth after spinal cord transection are accelerated by sustained l ‐DOPA administration (Doyle and Roberts 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, L-DOPA, a DA precursor (Fig. 1), enhances tail beat frequency and swimming speed in the European eel (Doyle & Roberts, 2004). L-DOPA also induced dominance in the Arctic charr (Salmonid), while high doses led to dyskinesia (Winberg and Nilsson, 1992).…”
Section: Dopamine and Locomotionmentioning
confidence: 98%
“…Treatments using quipazine (Antri et al, 2002; Barbeau and Rossignol, 1990; Feraboli-Lohnherr et al, 1999; Fong et al, 2005; Guertin, 2004a, b), clonidine (Barbeau and Rossignol, 1991; Chau et al, 1998; Cote et al, 2003), L-DOPA (Barbeau and Rossignol, 1991; Guertin, 2004b; De Mello et al, 2004; Doyle and Roberts, 2004; McEwen and Stehouwer, 2001), strychnine (De Leon et al, 1999b; Edgerton et al, 1997a, b), and/or bicuculline (Edgerton et al, 1997a, b; Robinson and Goldberger, 1986) have been shown to facilitate locomotor recovery. The enhanced synaptic transmission generated by using these drugs potentiates other treatments, including spinal cord stimulation and locomotor training, by lowering the activation threshold of the neurons associated with locomotion.…”
Section: Treatment Paradigms For Restoring Locomotor Control After a mentioning
confidence: 99%